Nutritional rickets among children admitted with severe pneumonia at Mulago hospital, Uganda: a cross-sectional study - Thereza Piloya; Beatrice Odongkara; Edward Maloba Were; Faith Ameda; Edison Mworozi; Paul Laigong (BMC, 2018)
Abstract Background There's abundant sunshine in the tropics but severe rickets is still observed. Nutritional rickets is associated with an increased risk of acute lower respiratory infections. Pneumonia is the leading cause of death in the under 5 -year old children with the highest burden in developing countries. Both Pneumonia and rickets are common in the developing countries and may affect clinical presentation and outcome. This study aimed to determine the prevalence and associated factors of nutritional rickets in children admitted with severe pneumonia. Methods This was a cross-sectional study of children aged 2-59 months presenting with severe pneumonia at an emergency unit. We enrolled 221 children between February and June 2012 after consent. A pre-coded questionnaire was used to collect data on socio-demographic, nutritional and past medical history. Physical exam was done for signs of rickets and anthropometric measurements. Serum calcium, phosphorus, and alkaline phosphatase (ALP) were assessed. Children with any physical signs of rickets or biochemical rickets (ALP > 400 IU); had a wrist x-ray done. Nutritional rickets was defined as the presence of radiological changes of cupping or fraying and/ or metaphyseal thickening. Severe pneumonia was defined using the WHO criteria. Statistical analysis was performed using the Stata 10 statistical package. P- value < 0.05 was significant. Results The prevalence of nutritional rickets among children with severe pneumonia is 9.5%. However, 14.5% had raised ALP (biochemical rickets). The factors independently associated with rickets was an elevated alkaline phosphatase; p-value < 0.001, or 32.95 95% CI (10.54-102.93). Other factors like breastfeeding, big family size, birth order were not significantly associated with rickets. Low serum calcium was detected in 22 (9.9%) of the 221 participants. Overall few children with rickets had typical clinical features of rickets on physical examination. Conclusion Rickets is a common problem in our setting despite ample sunshine. Clinicians should actively assess children for rickets in this setting and screen for rickets in those children at high risk even without clinical features.